Kontribusi Filolog dalam Pembuktian di Persidangan: Studi Kasus Konflik Agraria Masyarakat Sunda Wiwitan - Yamin Yamin (Manuskripta, 2019)
Abstract: This article examines the philologist's contribution in the evidentiary procedural law in court. There are two contributions of the philologist in the evidence in court, namely the evidence of the letter (in the form of a written document that is studied philologically) and the witness's statement that shows the authenticity and content of the text. In other words, philologists not only provide the text, but also explain the content of the text and the context. However, in practice in the Kuningan District Court, the evidence in the form of manuscripts and the testimony of philologist witnesses in civil procedural law tends to only fulfill the formality aspect, while the substance is not considered. The basic problem is that judges in civil procedural law tend to pursue formal truth, paying less attention to the substantial aspects. In addition, traditional law recorded in the form of codification efforts or merely charter, ethnographic descriptions, or juridical documents needs to receive serious attention from law enforcers in defending customary law communities. --- Abstrak: Makalah ini menguraikan kontribusi para filolog dalam menyajikan teks hukum dan peranannya dalam hukum acara pembuktian di pengadilan. Ada dua kontribusi filolog dalam pembuktian di pengadilan, yaitu alat bukti surat (yang berupa dokumen tertulis yang dikaji secara filologis) dan keterangan saksi yang menunjukkan keotentikan dan kandungan teks. Dengan kata lain, para filolog tidak hanya menyediakan teks, melainkan menjelaskan kandungan teks dan konteks. Namun, dalam praktiknya di Pengadilan Negeri Kuningan, alat bukti yang berupa manuskrip dan keterangan saksi filolog dalam hukum acara perdata cenderung hanya memenuhi aspek formalitas, sedangkan substansinya kurang dipertimbangkan. Problem mendasarnya adalah bahwa hakim dalam hukum acara perdata cenderung mengejar kebenaran formal, kurang memperhatikan aspek substansial. Di samping itu, hukum tradisi yang direkam dalam bentuk upaya kodifikasi atau sekadar piagam, deskripsi etnografi, atau dokumen yuridik perlu mendapat perhatian serius para penegak hukum dalam membela masyarakat hukum adat.